Silicon Lithium Ion Electrode Materials

By using magnesium thermal reduction and chemical vapor deposition technology to synthesize silicon-carbon composite materials in lithium-ion batteries, the problem of electrode rupture caused by volume changes in silicon anode materials in lithium-ion batteries is solved, and the effect of high capacity and cycle stability is achieved .

CN111936419BActive Publication Date: 2024-12-31RGT UNIV OF CALIFORNIA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201980016033.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-02-28
Filing Date
2019-02-27
Publication Date
2024-12-31
Estimated Expiration
2039-02-27

AI Technical Summary

Technical Problem

The silicon-based anode material in existing lithium-ion batteries causes electrode rupture and instability of the intermediate phase of solid electrolyte due to volume changes, resulting in irreversible capacity loss, limiting its practical application.

Method used

Using commercial silica water suspensions to synthesize silicon-carbon composites by spray drying and magnesium thermal reduction, using carbon coating and chemical vapor deposition techniques to form porous structures to adapt to volume changes during lithiation and deliquefaction, and improve Conductivity.

Benefits of technology

Achieved with high capacity and cycle stability, the silicon-carbon composite exhibits excellent capacity of 1835mAh g-1 and excellent stability of 100 cycles, and is cost-effective and scalable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111936419B_ABST
    Figure CN111936419B_ABST
Patent Text Reader

Abstract

Electrodes used in batteries include silicon-carbon composites and graphite. The silicon-carbon composite structure is microporous. Silicon-carbon composites can be manufactured by spray drying and magnesiothermal reduction of silicon, followed by carbon deposition.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of priority to U.S. Provisional Application No. 62 / 636,561, filed on February 28, 2018, which is incorporated herein by reference in its entirety. Technical Field

[0003] The present invention relates to battery cell devices and methods. In one embodiment, the present invention relates to lithium ion batteries. Background Art

[0004] Improved batteries, such as lithium-ion batteries, are desired. New materials and microstructures are desired to increase capacity and alleviate problems with silicon-based electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0005] Figures 1A to 1D Scanning electron microscope (SEM) and transmission electron microscope (TEM) images of silicon oxide nanoparticles.

[0006] Figures 2A to 2F SEM image of silicon oxide nanoparticles mixed with magnesium powder for magnesium thermal reaction.

[0007] Figure 3A X-ray crystallography (XRD) data of silicon oxide nanoparticles mixed with magnesium powder for magnesium thermal reaction are shown.

[0008] Figure 3B The kinetics of the isothermal step of the magnesium thermal reaction of silicon oxide nanoparticles are shown.

[0009] Figures 4A to 4D The isothermal temperature curve of the magnesium thermal reaction is shown.

[0010] Figure 4E Shows Figures 4A to 4D The conversion rate of the isothermal temperature curve.

[0011] Figure 4F Shows Figure 4E Ginstling-Brounshtein model fitting.

[0012] Figures 5A to 5B XRD data of the products of the magnesium thermal reaction are shown.

[0013] Figures 6A to 6E SEM image of the product of magnesium thermal reaction.

[0014] Figures 7A to 7E Lithiation-delithiation curve of the product of magnesium thermal reaction.

[0015] Figures 8A to 8ECapacitance-voltage curves of the products of the magnesium thermal reaction are shown.

[0016] Figures 9A to 9E TEM image of the product of magnesium thermal reaction.

[0017] Fig.9F Analysis of the surface area of ​​the products of the magnesium thermal reaction is shown.

[0018] Figures 10A to 10B Adsorption-desorption isotherm data for the products of the magnesium thermal reaction are shown.

[0019] Figures 11A to 11F Data on cycling stability, delithiation / lithiation, and initial coulombic efficiency (ICE) of silicon and silicon-carbon composites are shown.

[0020] Figures 12A to 12C SEM and TEM images of silicon-carbon composites.

[0021] Figures 13A to 13C Thermogravimetric analysis (TGA) analysis of the silicon-carbon composite is shown.

[0022] Figures 14A to 14D The cycling stability of the silicon-carbon-graphite hybrid anode is shown.

[0023] Fig.15A The cycling stability of the silicon-carbon-graphite anode is shown.

[0024] Figures 15B to 15C Representative charge and discharge voltage curves for a silicon-carbon-graphite anode are shown.

[0025] Fig.16 A battery according to one example of the present invention is shown.

[0026] Fig.17 A method of forming a battery according to one example of the present invention is shown. Summary of the invention

[0027] In the following detailed description, reference is made to the accompanying drawings, which form a part of the present invention, and in which specific embodiments in which the present invention may be implemented are shown by way of example. In the accompanying drawings, similar numbers throughout the multiple views describe substantially similar components. These embodiments are described in sufficient detail to enable those skilled in the art to implement the present invention. Other embodiments may be utilized, and structural or logical changes, etc. may be made without departing from the scope of the present invention.

[0028] A highly scalable and cost-effective synthetic route to produce silicon (Si) and silicon-carbon (Si-C) composites for Li-ion anode materials utilizes spray drying, magnesium thermal reduction, and chemical vapor deposition (CVD). A commercial nano-sized silica aqueous suspension (LUDOX HS-40) is used as a Si precursor. The diluted silica (SiO2) aqueous suspension is spray dried by an aerosol spray dryer. The spray-dried mixture of SiO2, magnesium (Mg) powder, and NaCl is then magnesium thermally reduced, with NaCl serving as a heat remover to maintain the porous structure as a secondary composite structure during the conversion of SiO2 to Si. After a thin layer of carbon is deposited on and in the pores by CVD, the Si-C composite shows a capacity of 1835 mAh g -1 As a promising anode material for Li-ion batteries, the Si-C / graphite hybrid thick electrode exhibits excellent performance, achieving 850 mAh g -1 The specific capacity and 3 mAh cm -2 The areal capacity of 200 cycles and the capacity retention rate of 9X compared with the second cycle.

[0029] Due to its ultra-high theoretical capacity of 4200mAh / g, silicon (Si) is a promising candidate as an anode material for next-generation lithium-ion (Li-ion) batteries. This capacity is 10 times higher than that of graphite, the most widely commercialized anode material. However, technical challenges such as the following hinder the practical application of Si-based anode materials: electrode rupture and particle crushing caused by volume changes of up to 300% during the transition between lithiation and delithiation, the formation of unstable solid electrolyte interphase (SEI), and the inherent poor conductivity of silicon. Particle crushing can be prevented by nanosizing Si particles below the critical rupture size. However, constant volume changes may make SEI unstable. The continuous decomposition of the electrolyte coupled with the poor conductivity of silicon leads to irreversible capacity loss, ultimately leading to battery failure.

[0030] Nowadays, the application of particles of silicon-graphite composite materials as hybrid anodes cannot solve the problem caused by the volume change of Si. Si-C composite materials are promising. The secondary structure of conformal carbon can be used to adapt to the volume change of silicon during lithiation and delithiation and provide better conductivity. Various nanostructures of Si-C composite materials have been reported, such as Si nanoparticles of sandwich structure, pomegranate-shaped Si-C, yolk-shell Si-C and carbon-coated Si. However, silicon of primary nanometer size is usually synthesized by liquid chemical method or chemical vapor deposition using silicon chloride (IV) (SiCl4) or pyrophoric silane (SiH4), which is expensive, environmentally unfriendly and non-scalable, limiting the commercial application of these methods.

[0031] Since SiO2 can be reduced by Mg, magnesium thermal reduction reaction (MRR) has attracted attention and is regarded as a promising synthesis method for Si. It is cheap and highly scalable. Si materials reduced by Mg exhibit good electrochemical properties. However, since the high local temperature may exceed the melting point of Si, it is difficult to maintain the original SiO2 structure during this violent exothermic reaction. Heat removers such as sodium chloride (NaCl) can be used to absorb the large amount of heat generated by MRR, thereby preventing Si nanoparticles from agglomerating and structural failure. Another challenge is the formation of by-products such as magnesium silicate (Mg2SiO4) or magnesium silicide (Mg2Si) during magnesium thermal reduction.

[0032] Here, high performance Si-C composites were synthesized by magnesium thermal reduction of spray-dried SiO2 derived from commercial SiO2 in the following reaction (1):

[0033] SiO2+2Mg→Si+2MgO (1)

[0034] Uniform carbon coating by chemical vapor deposition (CVD) can improve the conductivity of the composite material and promote the formation of a stable solid electrolyte interphase (SEI) layer on the Si surface. This is beneficial to the performance of the Si anode material. At the same time, the nano-sized Si particles generate void space during the magnesium thermal reduction reaction. The void space can alleviate particle crushing and accommodate the volume expansion of Si caused by lithiation.

[0035] First, prepare silicon. Dilute a commercial SiO2 aqueous suspension (LUDOX HS-40) with deionized water. Spray dry the obtained suspension at 120°C using a customized aerosol spray dryer. The spray-dried SiO2 obtained is further crushed and thoroughly mixed with magnesium (Mg) powder (300 mesh) at a molar ratio of Mg / SiO2=2.2:1 and sodium chloride (NaCl) at a mass ratio of Mg / NaCl=1:1 in a mechanical mixer for 1 hour. In a typical magnesium thermal reduction reaction (MRR), 270 mg of the mixture is sealed in a stainless steel reactor (5 mL) in an argon (Ar)-filled environment. The reactor is heated in a tube furnace at 1°C for 20 minutes. -1Slowly heat to 600 ℃ from room temperature, continue 1 hour, 3 hours, 6 hours, 9 hours and 12 hours respectively.After cooling to room temperature, the synthesized material is washed with 45mL 2M HCl solution (by volume, H2O: ethanol=1:1) for 12 hours to remove MgO and unreacted Mg, and then 1ml HF (49 weight %) is added to the solution to remove unreacted SiO2. The Si material obtained is washed with distilled water and ethanol and collected by vacuum filtration. The final product is dried in a vacuum oven for at least 12 hours.NaCl is studied as a heat remover in magnesium thermal reduction.

[0036] The carbon coating of the final product was carried out by CVD. Typically, 100 mg of Si-C composite material was loaded into a quartz tube reactor. After purging with Ar (100 sccm) for 60 minutes, the reactor was heated at 10 °C for 10 minutes. -1 The reactor was heated to 700°C at a heating rate of 1.50 ℃. After reaching this temperature, acetylene (C2H2) and argon gas mixture were introduced at a flow rate of C2H2 / Ar=10 / 20 sccm for 30 minutes while rotating the tubular reactor. Finally, during cooling to room temperature, acetylene was interrupted and argon was continued to be filled into the reactor, and the carbon-coated Si-C composite was collected.

[0037] The composition of the product was analyzed by X-ray diffraction (XRD). The internal morphology of Si and Si-C was analyzed by transmission electron microscopy (TEM) at an accelerating voltage of 120 kV. The surface morphology was observed under a scanning electron microscope (SEM). The surface area was calculated from N2 adsorption and desorption isotherms using the Brunauer-Emmett-Teller (BET) method. The pore size distribution was estimated by the Barrett-Joyner-Halenda (BJH) method.

[0038] Electrochemical measurements were performed using two-electrode button cells. The working electrode consisted of 80 wt% Si, 10 wt% sodium carboxymethylcellulose (CMC) as a binder, and 10 wt% carbon black (Super-P). The electrolyte consisted of a lithium hexafluorophosphate (LiPF6) solution (1 M) in a mixture of ethylene carbonate (EC), diethyl carbonate (DEC), and fluoroethylene carbonate (FEC) (EC:DEC:FEC = 45:45:10 by volume). Lithium foil was used as the counter electrode, and a porous polypropylene separator was used. For Li / Li + Galvanostatic cycling was performed from 0.01 V to 1.2 V with a current density of 100 mA g for the Si electrode. -1 , for Si-C thick electrode is 100mA g -1 and 500mA g -1 .

[0039] The morphology of SiO2 NPs was obtained by TEM ( Figure 1D ), after spray drying by an aerosol spray dryer, apple-shaped spray-dried SiO2 NP aggregates were obtained. Both TEM and SEM were performed to characterize the morphology, SEM images of particles at low magnification ( Figure 1A ) and high magnification SEM&TEM images in ( Figures 1B to 1C ) shows that SEM and EDX mapping was performed immediately after mixing SiO2, Mg and NaCl ( Figures 2A to 2F ). EDX mapping shows that the distribution of Si, O, Mg and Na elements is uniform.

[0040] The initial reaction was to mix spray-dried SiO2 and Mg in a stainless steel reactor at a molar ratio of 1:2.2. A thermocouple was used and placed inside the reactor to monitor the temperature in situ. The initial temperature of the MMR was about 540°C, and a huge temperature peak was observed. Figures 4A to 4F The temperature in the scene jumped to more than 1600℃, and micro Si particles and Mg2Si( Figures 3A to 3B ). Therefore, the extremely high local temperature may lead to the failure to maintain the original structure and the formation of by-products. Then, the heat remover NaCl was added to the Si precursor and Mg mixture. Three isothermal step temperatures were selected: 600°C, 700°C, and 800°C, and the isothermal times were set to 1 hour, 3 hours, 6 hours, 9 hours, and 12 hours. The measured in-situ isothermal step temperatures were 580°C, 680°C, and 780°C, respectively ( Figures 4A to 4F ), and all conversions under different reaction conditions were obtained. Figure 4E Both the temperature and the duration of the isothermal step are shown to contribute to the conversion. From the temperature monitoring graph, no huge temperature peak was observed after the start of the MRR. The conversion under each condition was the average of three experimental results. Using these conversions, kinetic studies were performed. The Ginstling-Brounshtein model was used, which is a kinetic model for solid-state reactions and is accurate for high yields. The average data was input into the model and the model fit is shown in Figure 4F The fitting results show that the rate constants at 580℃, 680℃ and 780℃ are 0.01 / hour, 0.0108 / hour and 0.0116 / hour respectively. Figure 3B The prediction of conversion at a certain time and temperature is shown in .

[0041] XRD was performed for all samples subjected to MRR at 580 °C for different durations, both after MRR and after acid treatment. Figure 5A) shows peaks indicating NaCl added as a heat remover, Si and MgO formed by the following reaction (2):

[0042] SiO2+2Mg→Si+MgO (2)

[0043] There is no trace of Mg2Si or Mg2SiO4 byproducts. MgO, unreacted SiO2 and NaCl were removed by etching with HCl and HF water / ethanol (volume / volume = 50 / 50) solution, and the XRD pattern of the sample after acid treatment ( Figure 5B ) shows that only pure silicon phase exists. According to the full length at half height of the peak and combined with the Sharrer equation, this indicates that a longer isothermal time is beneficial to crystal growth.

[0044] After MRR, the morphology and surface area changed significantly, and a clear trend of particle growth with increasing isothermal time was observed by TEM. A trend of porous structure evolution was also observed, with 1 hour ( Fig.9A ) and 3 hours ( Fig. 9B ) has a microporous structure, 6 hours ( Fig. 9C ) formed mesopores, 9 hours ( Fig.9D ) The porous structure disappears, and after 12 hours ( Fig.9E ) completely disappeared. The above materials were measured by 5-point surface area measurement ( Fig.9F ). The BET data show a clear decreasing trend in the surface area, which is associated with the growth of Si crystals.

[0045] All the above materials were made into button cells for electrochemical testing. Fig.11A The cycling stability and coulombic efficiency at a charge and discharge rate of 100 mA g are shown. The material under the condition of 6 h isothermal step time and 580 °C has the highest capacity and the best cycling stability after 100 cycles. In this case, the highest lithiation capacity is 3562 mAh g -1 , with a reversibility of 48%. After 100 cycles, it achieved a reversibility of 1344 mAh g -1 The 12 h material shows the worst cycling stability, which may be due to the larger Si particle size and smaller porosity. Fig. 11B The initial coulombic efficiency (ICE) of all the above materials based on two different calculation methods is shown. Fig. 11CIn the figure, the first group of columns represents reversibility (delithiation capacity / total lithiation capacity × 100%), and the second group of columns is silicon lithiation efficiency (Si lithiation capacity / total lithiation capacity × 100%), showing the terminology. From the ICE point of view, except for the reversibility of about 61% at 12 hours, the reversibility of 1 hour, 3 hours, 6 hours, and 9 hours is less than 50%. All of the above materials can achieve about 80% Si lithiation capacity, and there is a 30% gap between the two calculation methods, which indicates that about 30% of Li is captured and cannot be delithiated.

[0046] However, an ICE of less than 50% will not meet the requirements of practical applications. Carbon layers were deposited on the best performing spray-dried porous Si by CVD at different carbon ratios. The capacity and cycle stability of silicon products were improved. According to the ICE graph, the reversibility of porous Si was significantly improved by 30% at 9%, 12% and 16% carbon coatings, with ICEs of 82%, 76% and 76%, compared to 48% ICE of porous Si. The silicon lithiation efficiency was also improved by 5%. The initial lithiation capacity increased from 3562mAhg of porous Si to 160mAhg of porous Si. -1 This drops to 2951 mAh g at 9%, 12%, and 16% carbon ratios. -1 , 2690mAh g -1 and 2441mAh g -1 In this case, the Si-C composite with a carbon ratio of 12% has the best performance, which achieves 2690 mAh g -1 initial capacity and 76% ICE. After 100 cycles, it still has 1720mAh g -1 , it retains 83% capacity compared to the second cycle. 9重量% and Si-C 16重量% , the capacity maintained is 1642mAh g -1 and 1476mAh g -1 , and the capacity retention rates after 100 cycles were 74% and 79% relative to the 2nd cycle.

[0047] One of the most practical applications of Si-C is as an additional material for graphite anodes to increase capacity. 重量% As an additive and evaluated in electrodes of Si-C and commercial graphite, 4 wt% carboxymethyl cellulose binder, 1 wt% styrene-butadiene rubber, and 5 wt% acetylene black. The Si-C weight ratios were 10%, 20%, and 30%, and the corresponding graphite was 80%, 70%, and 60%. The electrode area mass loading was about 4 mg cm -2 , and a commercial graphite anode purchased from MTI (area loading 6.4 mg cm -2) was used as a reference. The anode was made into a button cell and electrochemical tests were performed. Figures 14A to 14D shows that at 0.5mAcm -2 Cycling stability and Coulombic efficiency at charge and discharge rates. Fig.14A The performance of Si-C / graphite hybrid anodes based on specific capacity was evaluated. Fig. 14B It is performance based on area capacity. Fig. 14C and 14D shows that at 1mAcm -2 Performance at current density.

[0048] With the help of Si-C composites, the anode performance is improved. Compared with commercial graphite anode (6.4 mg cm -2 )347mAhg -1 In comparison, 10 wt% (4.2 mg cm -2 )、20 wt% (4.0 mg cm -2 ) and 30 wt% (4.2 mg cm -2 )Si-C / graphite mixture at 0.5 mA cm -2 The initial specific capacity is 601 mAh g -1 , 848mAh g -1 and 1015mAh g -1 , compared to 2.2 mAh cm for graphite -2 , and the area capacity is 2.5 mAh cm -2 、3.4mAh cm -2 and 4.3 mAh cm -2 ICE from Si-C12 重量% The 76% of Si-C was slightly improved to 88% (10 wt% Si-C), 85% (20 wt% Si-C), and 84% (30 wt% Si-C), with a corresponding capacity of 416 mAh g after 200 cycles. -1 , 574mAh g -1 and 690mAh g -1 (174th cycle), the capacity retention rates relative to the second cycle were 95%, 92%, and 91% (174th cycle). -2 At a current density of 10 wt% (4.1 mg cm -2 ), 20 wt% (4.1 mg cm -2 ) and 30 wt% (4.2 mg cm -2 ) The Si-C / graphite hybrid still achieved 368 mAh g in the second cycle -1 , 526mAh g -1 and 626mAh g -1And during 200 cycles, the three types of anodes maintained 1.2 mAh cm -2 、1.8mAh cm -2 , 2.2mAh cm -2 However, the capacity of commercial graphite anodes has declined and only has an area capacity of less than 1 mAh cm -2 This is probably due to the inherent poor rate performance of graphite.

[0049] The paired Si-C / graphite anode and LiFePO4 cathode were assembled into a full cell, and the charge and discharge rate of the first cycle was 0.1 mA cm -2 Subsequently, 0.5 mA cm was applied for the remaining cycles. -2 or 1mAcm -2 The charging method uses constant current and constant voltage, with a cut-off current of 50 mA cm -2 . Figures 15A to 15C shows that at 0.5mAcm -2 and 1mA cm -2 The complete cycling stability and coulombic efficiency under 0.5 mA cm-2 show a clear improvement in specific capacity compared to a full cell paired with a commercial graphite anode and a LiFePO4 cathode. -2 During the current cycle, the Si-C / graphite anode reached 605 mAh g in the case of 20 wt% Si-C. -1 or 2.4 mAh cm -2 ICE is 85% accordingly. At 1mA cm -2 The Si-C / graphite anode still exhibits good rate performance and reaches 1.9 mAh cm in the case of 20 wt% Si-C. -2 Area capacity. Fig. 15B Excellent capacity retention is shown and is demonstrated by the stable charge and discharge voltage profiles at different cycles.

[0050] In summary, a cost-effective and highly scalable synthetic route for producing Si and Si-C composites was shown. The phenomenon of magnesium thermal reduction reaction was studied. Kinetic studies were performed and reaction constants were obtained. The Si nanoparticle size growth was successfully controlled and the porous structure was retained as a secondary structure. Due to the promising electrochemical performance, simple and controllable low temperature and low cost synthesis process, the Si-C composite is expected to be used in the next generation Li-ion battery anode.

[0051] Figure 1A is a scanning electron microscope (SEM) image of silicon oxide nanoparticles at low magnification. Figures 1B to 1CThis is a transmission electron microscope (TEM) image of silicon oxide nanoparticles at high magnification. Figure 1D is a TEM image of silicon oxide nanoparticles.

[0052] Figures 2A to 2F is a SEM image of silicon oxide nanoparticles mixed with magnesium powder for magnesium thermal reaction using energy dispersive x-ray spectroscopy (EDX) mapping.

[0053] Figure 3A X-ray crystallography (XRD) data of silicon oxide nanoparticles mixed with magnesium powder for magnesium thermal reaction at 580 degrees Celsius for 0 hours are shown.

[0054] Figure 3B Kinetic conversion predictions calculated from rate constants obtained from the isothermal step of the magnesium thermal reaction of silicon oxide nanoparticles are shown.

[0055] Figures 4A to 4D The isothermal temperature curve of the magnesium thermal reaction is shown. Figure 4A Isothermal temperature curves at 600°C in the presence of NaCl at 1 hour, 3 hours, 6 hours, 9 hours and 12 hours are shown. Figure 4B Isothermal temperature curves at 700°C in the presence of NaCl at 1 hour, 3 hours, 6 hours, 9 hours and 12 hours are shown. Figure 4C Isothermal temperature curves at 800°C in the presence of NaCl at 1 hour, 3 hours, 6 hours, 9 hours and 12 hours are shown. Figure 4D The isothermal temperature curve at 600° C. at 0 hours in the absence of NaCl is shown.

[0056] Figure 4E Shows Figures 4A to 4D The conversion rate of the isothermal temperature curve (the average of three times under the above conditions).

[0057] Figure 4F Shows Figure 4E The conversion rate was fitted by the Ginstling-Brounshtein model.

[0058] Figure 5A XRD data of the products of magnesium thermal reaction at 580° C. for 1 hour, 3 hours, 6 hours, 9 hours and 12 hours in the presence of NaCl (Mg:NaCl=1:1) are shown. Figure 5B Shows Figure 5A XRD data of the product after acid washing.

[0059] Figures 6A to 6Eare SEM images of the products of magnesium thermal reaction at 580° C. in the presence of NaCl (Mg:NaCl=1:1) for 1 hour, 3 hours, 6 hours, 9 hours and 12 hours.

[0060] Figures 7A to 7E 1 are representative first lithiation-delithiation curves of the products of magnesium thermal reaction at 580° C. for 1 hour, 3 hours, 6 hours, 9 hours and 12 hours in the presence of NaCl (Mg:NaCl=1:1).

[0061] Figures 8A to 8E Capacitance-voltage (CV) curves of the products of magnesium thermal reaction at 580° C. for 1 hour, 3 hours, 6 hours, 9 hours and 12 hours in the presence of NaCl (Mg:NaCl=1:1) are shown.

[0062] Figures 9A to 9E is a TEM image of the product of magnesium thermal reaction particles to show the details of the microstructure.

[0063] Fig.9F A 5-point analysis of the surface area of ​​the products of the magnesium thermal reaction is shown.

[0064] Figure 10 shows an inset of the N2 adsorption-desorption isotherm and pore size distribution using BET surface area data for spray-dried SiO2, which has a BET surface area of ​​178 m2 g -1 .

[0065] Fig.11A The above five products are shown in Figure 1 at 100 mA g -1 The cycling stability under 40 ℃ and 80 ℃ (average value of 3 electrodes). Fig. 11B Delithiation and lithiation curves (6 hours) of Si are shown with nomenclature. Fig. 11C The ICE of Si based on two calculation methods is shown. Fig.11D The Si-C sample is shown in Figure 2 at 100 mA g -1 The cycling stability under 40 ℃ and 80 ℃ (average value of 3 electrodes). Fig.11E Delithiation and lithiation curves of Si-C (12 wt %) are shown with nomenclature. Fig.11F The ICE based on two calculation methods for Si-C samples is shown.

[0066] Fig. 12A is the SEM image of Si-C composite material. Figures 12B to 12C is the TEM image of Si-C composite material.

[0067] Figures 13A to 13C is the TGA of Si-C composites with 9 wt%, 12 wt% and 16 wt% carbon ratios.

[0068] Fig.14A The results show that the 10 wt %, 20 wt % and 30 wt % Si-C / graphite hybrid anodes have good thermal conductivity at 0.5 mA cm -2 Cycling stability based on specific capacity under . Fig. 14B shows that at 0.5 mA cm -2 Cycling stability based on area capacity under . Fig. 14C The results show that the 10 wt %, 20 wt % and 30 wt % Si-C / graphite hybrid anodes have good thermal conductivity at 1 mA cm -2 Cycling stability based on specific capacity under . Fig.14D shows that at 1 mA cm -2 Cycling stability based on area capacity under .

[0069] Fig.15A The full cell of Si-C / graphite and LiFePO4 is shown at 0.5 mA cm -2 Cycling stability based on specific capacity under . Fig. 15B shows that at 0.5 mA cm -2 Representative charge and discharge voltage curves under . Fig. 15C shows that at 1mAcm -2 Representative charge and discharge voltage curves under .

[0070] Fig.16 An example of a battery 100 according to an embodiment of the present invention is shown. The battery 100 is shown to include an anode 110 and a cathode 112. An electrolyte 114 is shown between the anode 110 and the cathode 112. In one example, the battery 100 is a lithium ion battery. In one example, the anode 110 includes sulfur as described in the above example. In one example, the cathode 112 includes silicon as described in the above example. In one example, although the present invention is not limited thereto, the battery 100 is formed to conform to a 2032 button-type form factor.

[0071] Fig.17 A method of forming a battery according to one example of the present invention is shown. The method includes spray drying silicon oxide nanoparticles (step 202), magnesium thermally reducing the silicon oxide nanoparticles to produce porous silicon (step 204), and coating the porous silicon with carbon (step 206).

[0072] To better illustrate the methods and apparatus disclosed herein, a non-limiting list of embodiments is provided herein:

[0073] Embodiment 1 includes an electrode. The electrode comprises a silicon-carbon composite material and graphite. The silicon-carbon composite material comprises a porous silicon substrate and a carbon layer on the porous silicon substrate.

[0074] Embodiment 2 includes the electrode of embodiment 1, wherein the porous silicon substrate includes pores, a majority of the pores having a diameter of 2 nanometers or less.

[0075] Embodiment 3 includes the electrode of any of embodiments 1-2, wherein the porous silicon substrate includes pores, a majority of the pores having a diameter of 2 nanometers to 50 nanometers.

[0076] Embodiment 4 includes the electrode of any of Embodiments 1 to 3, wherein the porous silicon substrate includes pores having a first distribution and pores having a second distribution, wherein the first distribution is different from the second distribution.

[0077] Embodiment 5 includes the electrode according to any one of embodiments 1 to 4, wherein the surface area of ​​the porous silicon substrate is 22.6 m 2 g -1 Up to 178.0m 2 g -1 .

[0078] Embodiment 6 includes the electrode according to any one of embodiments 1 to 5, wherein the surface area of ​​the porous silicon substrate is 50.0 m 2 g -1 Up to 100.0m 2 g -1 .

[0079] Embodiment 7 includes the electrode according to any one of embodiments 1 to 6, wherein the carbon layer accounts for 9 wt % to 16 wt % of the total.

[0080] Embodiment 8 includes the electrode of any of Embodiments 1 to 7, wherein the carbon layer comprises 12 weight percent.

[0081] Embodiment 9 includes the electrode according to any one of embodiments 1 to 8, wherein the initial specific capacity is 600 mAh g -1 Up to 1020mAh g -1 .

[0082] Embodiment 10 includes the electrode of any one of embodiments 1 to 9, wherein the conversion efficiency of the electrode is 60% to 90%.

[0083] Example 11 includes a method of making an electrode material, comprising: spray drying silicon oxide nanoparticles, magnesium thermally reducing the silicon oxide nanoparticles to produce porous silicon, and coating the porous silicon with carbon to produce a silicon-carbon composite material.

[0084] Embodiment 12 includes the method of embodiment 11, wherein thermally reducing the silicon oxide magnesium includes mechanically mixing the silicon oxide with the magnesium and the heat removal agent to form a mixture.

[0085] Embodiment 13 includes the method of any one of embodiments 11 to 12, wherein thermally reducing the magnesium silicon oxide includes maintaining the reaction at an isothermal step for 1 hour to 12 hours.

[0086] Embodiment 14 includes the method of any one of embodiments 11 to 13, wherein the isothermal step is from 1 hour to 6 hours.

[0087] Embodiment 15 includes the method of any one of embodiments 11 to 14, wherein thermally reducing the magnesium silicon oxide includes an isothermal step at 600 degrees Celsius, 700 degrees Celsius, or 800 degrees Celsius.

[0088] Embodiment 16 includes the method of any one of Embodiments 11 to 15, further comprising filling the silicon-carbon composite with graphite.

[0089] Embodiment 17 includes the method of any of Embodiments 11 to 16, wherein the graphite comprises 70 wt % to 90 wt % of the electrode material.

[0090] Embodiment 18 includes an electrode manufactured by the method according to Embodiment 12.

[0091] Embodiment 19 includes an electrode according to Embodiment 18, wherein a majority of the pores have a diameter of 2 nanometers or less.

[0092] Embodiment 20 includes the electrode of any of Embodiments 18-19, wherein the majority of the pores have a diameter of 2 nanometers to 50 nanometers.

[0093] Throughout this specification, multiple instances can implement the parts, operations or structures described as single instances. Although the individual operations of one or more methods are shown and described as independent operations, one or more individual operations can be performed simultaneously, and it is not necessary to operate in the order shown. The structures and functions presented as independent components in the exemplary configuration can be implemented as combined structures or components. Similarly, the structures and functions presented as individual components can be implemented as independent components. These variations, modifications, additions and improvements and other variations, modifications, additions and improvements fall within the scope of the subject matter of this paper.

[0094] Although an overview of the subject matter of the present invention has been described with reference to specific exemplary embodiments, various modifications and changes may be made to these embodiments without departing from the broader scope of the embodiments of the present disclosure. For convenience only, these embodiments of the subject matter of the present invention may be referred to herein individually or collectively by the term "invention", and if more than one disclosure or inventive concept is actually disclosed, it is not intended to automatically limit the scope of the present application to any single disclosure or inventive concept.

[0095] The embodiments shown herein are described in sufficient detail to enable those skilled in the art to practice the disclosed teachings. Other embodiments may be used and derived therefrom, so that structural and logical substitutions and changes may be made without departing from the scope of the present disclosure. Therefore, the invention should not be understood in a restrictive sense, and the scope of the various embodiments is limited only by the appended claims and the full scope of equivalents given by these claims.

[0096] As used herein, the term "or" can be interpreted in an inclusive or exclusive sense. In addition, multiple instances can be provided for resources, operations or structures described as a single instance herein. In addition, the boundaries between various resources, operations, modules, engines and data storage are arbitrary to some extent, and specific operations are shown in the context of specific illustrative configurations. Other configurations of functions are foreseeable and can fall within the scope of various embodiments of the present disclosure. Generally, the structures and functions presented as independent resources in the exemplary configuration can be implemented as combined structures or resources. Similarly, the structures and functions presented as single resources can be implemented as independent resources. These variations, modifications, additions and improvements and other variations, modifications, additions and improvements fall within the scope of the embodiments of the present disclosure as represented by the appended claims. Therefore, the specification and the accompanying drawings should be considered to be illustrative rather than restrictive.

[0097] For purposes of illustration, the foregoing description has been described with reference to specific exemplary embodiments. However, the above illustrative discussion is not intended to be exhaustive or to limit the possible exemplary embodiments to the precise form disclosed. In view of the above teachings, many modifications and variations are possible. The exemplary embodiments were chosen and described in order to best illustrate the principles involved and their practical application, thereby enabling others skilled in the art to best utilize the various exemplary embodiments with various modifications suitable for the particular use contemplated.

[0098] It should also be understood that, although the terms "first", "second" etc. can be used in this article to describe multiple elements, these elements should not be limited by these terms. These terms are only used to distinguish one element from another element. For example, without departing from the scope of the exemplary embodiment of the present invention, the first contact can be referred to as the second contact, and similarly, the second contact can be referred to as the first contact. Both the first contact and the second contact are contacts, but they are not identical contacts.

[0099] The terms used in the description of the exemplary embodiments herein are only used for the purpose of describing specific exemplary embodiments and are not intended to be restrictive. Unless the context clearly indicates otherwise, as used in the description of the exemplary embodiments and the attached examples, nouns modified by quantifiers are intended to also include plural forms. It should also be understood that the term "and / or" as used herein refers to and encompasses any possible combination and all possible combinations of one or more related enumerated items. It will also be understood that when used in this specification, the term "includes" and / or "comprising" refers to the presence of the features, integers, steps, operations, elements and / or parts, but does not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or their groups.

[0100] Depending on the context, the term "if" as used herein may be interpreted to mean "when" or "at the time of" or "in response to determining" or "in response to detecting". Similarly, depending on the context, the phrase "if determined" or "if (the condition or event) is detected" may be interpreted to mean "at the time of determination" or "in response to determining" or "when (the condition or event) is detected" or "in response to detecting (the condition or event)".

Claims

1. A method for manufacturing an electrode material, comprising: spray drying silicon oxide nanoparticles; adding NaCl to the silicon oxide nanoparticles during magnesium thermal reduction to control morphology; magnesium thermally reducing the silicon oxide nanoparticles to produce porous silicon; coating the porous silicon with carbon to produce a silicon-carbon composite of carbon-coated porous silicon particles; as well as Graphite electrodes were added to the carbon-coated porous silicon particles.

2. The method of claim 1, wherein thermally reducing the silicon oxide magnesium comprises mechanically mixing the silicon oxide with magnesium and a heat remover to form a mixture.

3. The method of claim 2, wherein thermally reducing the magnesium silicon oxide comprises maintaining the reaction at an isothermal step for 1 hour to 12 hours. The method according to claim 3 , wherein the isothermal step is from 1 hour to 6 hours.

5. The method of claim 3, wherein thermally reducing the magnesium silicon oxide comprises an isothermal step at 600 degrees Celsius, 700 degrees Celsius, or 800 degrees Celsius.

6. The method of claim 1, wherein the graphite comprises 70 to 90 weight percent of the electrode material.

7. An electrode manufactured by the method according to claim 1.

8. The electrode according to claim 7, wherein the diameter of most of the pores is 2 nanometers or less.

9. The electrode according to claim 7, wherein the diameter of most of the pores is 2 nm to 50 nm.